Develop fundamental principles for a strategic framework that incorporates the combination and integration of business ecosystems - Abdullah, Edwin Hidayat; Sijabat, Rosdiana; Susilo, Wilhelmus Hary; Herusetya, Antonius (Edelweiss Applied Science and Technology, 2024)
This study aimed to investigate the fundamental strategic principles necessary for achieving a competitive advantage by promoting business growth through the identification of synergies within the business ecosystem and the comprehensive integration of the business environment. A qualitative research methodology was employed, with a design focused on an extensive literature review. The analysis was based on 32 pertinent scholarly articles related to the primary themes of interest. Data analysis was performed using NVivo software to facilitate the literature review process. The findings underscored the theoretical enhancement of business strategies among stakeholders to secure a competitive edge. This included an assessment of the impact of policies on strategic consolidation within the holding company, while highlighting the significance of the business ecosystem in bolstering competitiveness. The research emphasized the creation of synergies as a means to achieve a competitive advantage and the alignment of members through the integration of the business ecosystem.